The relationship of teachers’ ideas about children’s participation with their support of children’s opinions and involvement in decision-making - Liudmila M. Ursulenko (Современное дошкольное образование)
Background. Teachers’ ideas have a significant impact on their practical decisions. Supporting the child’s opinion and participation in decision-making helps children develop a sense of belonging and self-expression, which in turn has a positive effect on both educational achievement and overall quality of life. Nevertheless, issues related to teachers’ ideas of the concept of participation and its implementation in the study group remain insufficiently investigated.